In vitro maturation of the cisternal organelle in the hippocampal neuron's axon initial segment - Sánchez-Ponce, Diana; DeFelipe, Javier; Garrido, Juan José; Muñoz, Alberto (Molecular and cellular neuroscience, 2011)
Regulation of Ca2+ concentrations is essential to maintain the structure and function of the axon initial segment (AIS). The so-called cisternal organelle of the AIS is a structure involved in this regulation, although little is known as to how this organelle matures and is stabilized. Here we describe how the cisternal organelle develops in cultured hippocampal neurons and the interactions that facilitate its stabilization in the AIS. We also characterize the developmental expression of molecules involved in Ca2+ regulation in the AIS. Our results indicate that synaptopodin (synpo) positive elements considered to be associated to the cisternal organelle are present in the AIS after six days in vitro. There are largely overlapping microdomains containing the inositol 1,4,5-triphosphate receptor 1 (IP3R1) and the Ca2+ binding protein annexin 6, suggesting that the regulation of Ca2+ concentrations in the AIS is sensitive to IP3 and subject to regulation by annexin 6. The expression of synpo, IP3R1 and annexin 6 in the AIS is independent of the neuron activity, as it was unaffected by tetrodotoxin blockage of action potentials and it was resistant to detergent extraction, indicating that these proteins interact with scaffolding and/or cytoskeleton proteins. The presence of ankyrin G seems to be required for the acquisition and maintenance of the cisternal organelle, while the integrity of the actin cytoskeleton must be maintained for the expression IP3R1 and annexin 6 to persist in the AIS.